Postmodernist parodies, fantastics and carnivalesques: the figure of the mask in Noticias del Imperio - Rodríguez Muñoz, Edwin Steven (Interpretextos revista semestral de creación y divulgación de las humanidades (Colima), 2024)
In Noticias del Imperio, by Fernando Del Paso, its parodic content is evident, due to the recreation of key figures and moments in the history of Mexico. Some of these characters hide behind a mask that, analyzed from postmodernist parody (Hutcheon, 1991), the fantastic (Todorov, 2021) and the carnival (Bajtín, 1979), encodes a message to the reader through symbology. This article delves into the analysis of these masks, linking them with elements of irony and polyphony, with the aim of evidencing the way in which Del Paso seeks to deconstruct part of history, opening the door to a reevaluation by the reader.